Chinese herbal medicine for myasthenia gravis: A systematic review and meta-analysis of randomized clinical trials - Si-jia Zhu; Rui-ting Wang; Ze-yu Yu; Ruo-xiang Zheng; Chang-hao Liang; You-you Zheng; Min Fang; Mei Han; Jian-ping Liu (Integrative Medicine Research)
Background: Myasthenia Gravis (MG) is a disorder of neuromuscular transmission bringing mild ocular weakness to severe generalized muscle weakness and disability. The conventional treatments have long-term side effects, and Chinese herbal medicines (CHM) have shown possible effect and safety for MG patients, but the existing evidence was not robust enough and the results were out of date. Methods: Searching for randomized controlled trials (RCTs) was conducted in 7 databases and clinical trial registries until July 2021. The ROB 2 tool was used to assess the study quality and GRADE was used to assess the quality of whole evidence. Meta-analyses were conducted and the results were presented as risk ratio (RR) or mean difference (MD) with 95% confidence interval (CI). Results: Nineteen RCTs (1283 participants) testing 13 kinds of CHM with adequate randomization were included and six RCTs investigating Compound Huangqi were included in the meta-analyses. In addition to conventional treatment, nine CHMs reduced symptom scores of MG. Compound Huangqi plus conventional treatment (pyridostigmine bromide or prednisone or both) reduced the symptom scores compared with conventional treatment (MD = -3.56, 95%CI -4.86 to -2.26). Less adverse events happened in the CHM groups (3/247 in the CHM groups, 52/245 in the control groups, RR = 0.13, 95%CI 0.06 to 0.30, 9 RCTs, a total of 492 participants). The effect on quality of life was inconsistent. Conclusion: Nine CHMs could probably bring benefit for MG symptom improvement. Moderate to low certainty of evidence supported Compound Huangqi added-on conventional treatment probably bring extra benefit of improving MG symptoms. Adding CHMs could be safer than giving only conventional treatment. Study registration: The protocol was registered in PROSPERO (ID: 32718).